2019
DOI: 10.3390/plants9010043
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Karrikins as Novel Plant Growth Regulators in Agriculture

Abstract: Karrikins (KARs) have been identified as molecules derived from plant material smoke, which have the capacity to enhance seed germination for a wide range of plant species. However, KARs were observed to not only impact seed germination but also observed to influence several biological processes. The plants defected in the KARs signaling pathway were observed to grow differently with several morphological changes. The observation of KARs as a growth regulator in plants leads to the search for an endogenous KAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 80 publications
(108 reference statements)
0
15
0
2
Order By: Relevance
“…In addition, biochar contains substantial quantities of minerals such as calcium and magnesium and inorganic carbonates, which is beneficial for plant growth. Biochar may improve soil productivity, soil permeability, and carbon sequestration [32][33][34][35][36]. Zhu et al [37] indicated that biochar could enhance yield by stimulating microbe activity in the rhizosphere and improving soil water holding capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, biochar contains substantial quantities of minerals such as calcium and magnesium and inorganic carbonates, which is beneficial for plant growth. Biochar may improve soil productivity, soil permeability, and carbon sequestration [32][33][34][35][36]. Zhu et al [37] indicated that biochar could enhance yield by stimulating microbe activity in the rhizosphere and improving soil water holding capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The shared impact of plastic film mulching with biochar on ET, crop yield, and WUE as a ridge-furrow rainwater harvesting technology in China are currently less understood (Nelissen et al, 2012;Fischer et al, 2019). Therefore, understanding how biomass in China and across the world can change under the combined application of plastic film and biochar and processes activated as a result of these changes is key to harnessing their potential for wider use in agriculture (Antala et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Karrikin is a group of chemical compound involved in plant seed germination and early development, it has been shown to be involved in phytohormone signaling networks [42]. Current understandings on karrikins are primarily in plant growth, therefore, it would be interesting to further investigate whether this response to karrikin is also involved in disease defense [42, 43]. Interestingly, gene loss events are usually associated with transporter and secondary metabolism in Valsa species but they never loss the function suggesting gene loss by Valsa species are more of a redundancy reduction rather than purge of certain function.…”
Section: Discussionmentioning
confidence: 99%